Impact assessment of climate change on hydro-climatic conditions of arid and semi-arid watersheds (case study: Zoshk-Abardeh watershed, Iran) - Mohadese Rahimpour (IWA Publishing, 2021)
The hydrologic cycle in the river basins of semi-arid regions is severely influenced by climate change. The aim of this study is to assess the impact of climate change on the hydro-climatic condition in Zoshk-Abardeh watershed in eastern Iran. The Soil and Water Assessment Tool (SWAT) was calibrated using the Sequential Uncertainty Fitting – Version 2 (SUFI-2) algorithm to improve the simulation results of the runoff. The Model for Interdisciplinary Research on Climate-Earth System Models (MIROC-ESM) was used to investigate the effects of climate change on hydro-climatic components under the representative concentration pathway scenarios (RCPs: 2.6, 4.5, 6.0, and 8.5) and in near- (2014–2042), mid- (2042–2071), and far- (2072–2100) futures. The temperature component under the RCP4.5 and RCP6.0 during the near- and mid-future intervals and the far-future period (for RCP6.0) indicated a significant rising trend. The rainfall parameter in all RCPs and future intervals showed an insignificant descending trend. Runoff alterations under the RCP4.5 amid the mid- to far-future intervals and under the RCP8.5 throughout the far-future period trailed a significant descending trend. The results determined that the temperature will track an upward tendency, while precipitation and runoff will follow a descending trend in this watershed by the end of the 21st century.